Ulcerative Colitis complicated by lower limbs thromboemboilism- an unusual case scenario - Singh, Harpreet; Mathur, Rekha; Kaur, Parminder; Tanwar, Vikram (Journal of Advances in Internal Medicine, 2015)
Patients with inflammatory bowel disease (IBD) have an increased risk of vascular complications. In ulcerative colitis, 10% of deaths are attributed to thromoembolic complications. Arterial thromboembolic complications (ATEs) occur less frequently than venous thromoembolism (VTEs) in IBD patients. They are more common after interventional or surgical procedure but they can also occur spontaneously. Both venous and arterial, are serious extra-intestinal manifestations complicating the course of inflammatory bowel disease (IBD) and can lead to significant morbidity and mortality. Although there is no consensus regarding use of anticoagulants yet timely treatment of thrombosis in ulcerative colitis with anticoagulant therapy shows good results. Journal of Advances in Internal Medicine 2015;04(01):28-30